2013
DOI: 10.2215/cjn.08700812
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Concentrations of β-Trace Protein, β2-Microglobulin, Cystatin C, and Creatinine in the US Population

Abstract: SummaryBackground and objectives b-trace protein (bTP), b2-microglobulin (b2M), and cystatin C (CysC) have advantages over creatinine for estimating GFR and prognosis. This study compares the distribution of all four markers in the general population and their associations with possible determinants of GFR.Design, setting, participants, & measurements bTP and b2M were measured in 7596 participants (aged $12 years) of the Third National Health and Nutrition Examination Survey (1988)(1989)(1990)(1991)(1992)(1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 36 publications
(44 reference statements)
4
49
1
Order By: Relevance
“…9,29,44 Similarly in NHANES III, several factors are associated with higher serum BTP and B2M, including older age, hypertension, higher CRP, and lower HDL-cholesterol, whereas female sex and non-Hispanic black and Hispanic race/ethnicity are associated with lower BTP and lower body mass index is associated with lower B2M. 45 Some have suggested that BTP may play a role in cardiovascular disease, potentially through atherosclerotic pathways. BTP expression has been observed in heart tissue and BTP accumulation has been observed in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 98%
“…9,29,44 Similarly in NHANES III, several factors are associated with higher serum BTP and B2M, including older age, hypertension, higher CRP, and lower HDL-cholesterol, whereas female sex and non-Hispanic black and Hispanic race/ethnicity are associated with lower BTP and lower body mass index is associated with lower B2M. 45 Some have suggested that BTP may play a role in cardiovascular disease, potentially through atherosclerotic pathways. BTP expression has been observed in heart tissue and BTP accumulation has been observed in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 98%
“…In NHANES III, elevated BTP and B2M were associated with several factors that can also increase ESRD or mortality risk, including higher age, higher body mass index, hypertension, higher C-reactive protein, and lower HDL cholesterol for elevated B2M and higher age, male sex, race/ethnicity, hypertension, higher C-reactive protein, and lower HDL cholesterol for elevated BTP. 23 Serum B2M is also elevated in multiple myeloma and is part of risk stratification guidelines for this condition. 24 Additional potential non-GFR determinants for elevated BTP include genetic factors, cardiovascular disease, pregnancy, muscle mass, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated B2M in our large amputee group may be attributable to chronic inflammation. Modestly increased CRP is associated with elevated levels of B2M, but not BTP, SCr, or cystatin C [29]. Amputation is associated with increased pulse wave forms and increased pulse wave forms are associated with inflammation and elevated CRP [30,31,32].…”
Section: Discussionmentioning
confidence: 99%